Analisis Kelayakan Lokasi dan Finansial Pembangunan Industri Pengolahan Kakao di Pesisir Timur Provinsi Aceh - T. Saiful Bahri (Jurnal Agrisep, 2014)
Abstract. East coast of Aceh province is one of the centers of cocoa production in the province of Aceh with an area of 55 077 hectares of crops and production reached 22 748 tons of dry beans in 2012. The increase in the value of the additional cocoa made with an effort to build a cocoa processing unit, for the construction of the processing unit needs analysis of industrial location and investment. Technically, the development of cocoa bean processing industry in the eastern region of Aceh has the potential to be built in the district of Bandar Baru Pidie Jaya district, and in the District of Rantau Peureulak East Aceh district. Value of fixed capital investment development flour and fat processing plant is on the east coast of Aceh with a capacity of 20 tons per day is IDR 51.476.575.000 and operating expenses of IDR 134.358.106.250 per year. The products produced in the form as much as 1,440 tons of cocoa powder and cocoa butter 1,760 tons per year with estimated revenues IDR 146.88 billion per year, the net income (net benefit) is IDR 12.521.893.750 per year. Up to 20-year economic life of the plant, then the NPV obtained IDR 29.698.765.000; IRR 23,63; Net B / C of 1,58 with a payback period of 6 years 7 months. Break even calculation results well below the capacity of the plant and the cost is also far below the estimated selling price of flour and cocoa butter, cocoa processing plant in Aceh feasible to develop.